Modalização em artigos científicos da área da Linguística - Andrade, Valdete Aparecida Borges (2010)
This dissertation aims to analyze the manifestation of the modalities in the genre scientific paper in the field of Linguistics and the functions they have in the texts as the speaker s attitude markers through searching for regularities in their use in these functions and verifying their relationship with the argumentation in such genre. Thus, we aim to: i) identify the modalities which are used in the scientific papers, as well as the most used modal markers; ii) verify the functions that the modal markers have in the scientific papers of the Linguistics field and how such functions are related to the argumentative role in this genre; iii) identify the regularities/generalizations in the functioning of linguistics modalities in the genre scientific paper; iv) verify whether certain modalities correlate with moves in scientific papers such as: to propose, to attack and to defend an idea, to propose an idea keeping it from possible questioning, etc ; v) verify possible regular correlations between form (modal markers), current modalities and: a) modalities functions; b) categories of the superstructure of the scientific paper. We know that when writing texts people always resort to modal markers, standardizing language. Our hypothesis is that modalities and standardization are also used in the scientific paper as a regularity; that there are correlations between modalities and the superstructure of the scientific paper and between modalities and certain functions or moves inside the scientific paper; that in scientific papers the modalities play roles related to argumentation; and that alethic and epistemic modalities are established, in the scientific genre of the field of linguistics, as basic. For such research, we did firstly a theoretical study of text and discourse according to different authors, we then analyzed the modalities in correlation with the superstructure of the scientific paper according Van Dijk studies (1983 apud TRAVAGLIA, 1991) and Castro (1996) and then we proposed a superstructure that we consider relevant for our study with emphasis to the basic criterion required by this area. For the investigation of the argumentative structure we adopted the theory of Perelman and Olbrechts-Tyteca (2002). The methodology we have opted for is qualitative and quantitative focusing on the linguistic and social aspects of the genre scientific paper in the field of Linguistics. In this study, we used the label of the modalities which was re-elaborated by Travaglia (1991) from the proposed label by Koch (1996), Guimarães (1979) and Travaglia (1981) so as to analyze the different modalities which are expressed by several linguistic resources. The definition of the linguistic modalities was elaborated taking into consideration several authors. For such definition we resorted to the theoretical contributions of Travaglia (1991), Coracini (1991), Barros (2007), Bentes (2005), Koch (1996), Palmer (1986) and Guimarães (1979). In this study, we have come to the conclusion that the authors/producers use the epistemic modalities in the construction of the text. Otherwise, we have verified that this type of modality establish different functions for each one of those parts of the superstructure of the text. As for the volition modality it is present in the introduction and in the final of the conclusions so as to mark intentions and pretentions. We also verified, as a regularity that we have found, that in the scientific papers the most used modalities are epistemic, alethic and volition, while the deontics and imperative ones are little used.